Synthesis and blend of bio-based benzoxazines from cardanol and diphenolic acid - Viet, Cao Xuan; Thanh, Nguyen Thi Le; Lan, Du Ngoc Uy (Vietnam Journal of Science and Technology, 2020)
In this study, two benzoxazine monomers, m-alkylphenyl-3,4-dihydro-2H-benzoxazine (CA-Bz) and 4,40-Bis-[6-(3-phenyl-3,4-dihydro-2H-1, 3-benzoxazine)] pentanoic acid (DPA-Bz) were successfully synthesized from fully bio-based phenols (cardanol and diphenolic acid). Their structures were confirmed by FTIR and NMR spectroscopy. CA-Bz/DPA-Bz blend with weight ratio of 3:1 was prepared and polymerization of the monomers were characterized by DSC. The ring-opening polymerization of CA-Bz was found to decrease significantly by incorporation of carboxyl groups in DPA-Bz showing thereby the catalytic effect of acid functionality. The modified polybenzoxazine also showed an enhancement of the thermal properties.